Optical polarization study in the open cluster NGC 6250 - Feinstein Baigorri, Carlos (2008)
We present (UBVRI) multicolour linear polarimetric data for 32 of the brightest stars in the area of the open cluster NGC 6250, with the aim of studying the properties of the interstellar medium (ISM) towards the cluster. Our data yield a mean polarization per cent, close to the polarization value produced by the ISM with normal efficiency for a mean colour excess of E B- V = 0.37. Our analysis indicates that the observed visual absorption in NGC 6250 is caused by a nearby dust layer (within 300 pc) producing a polarization with an angle close to the Galactic plane (θGP ∼ 38°). In addition, there are at least two more dust layers along the line of sight between the Sun and the cluster producing a change in the observed polarization, making our results compatible with Neckel and Klare's results. The observations show differences between the orientation of the local magnetic field of the nearby dust layer and the one that is polarizing along the way to the cluster (Δθv = 20°). The internal dispersion of the polarization values for the members of NGC 6250 seems to be compatible with the presence of intracluster dust. The majority of observed stars do not present evidence of intrinsic polarization in their light. In this work, we also show (as in several previous papers) how polarimetry is an excellent technique for identifying non-member stars.